Milk fat globule membrane supplementation to obese rats during pregnancy and lactation promotes neurodevelopment in offspring via modulating gut microbiota - Yuan, Qichen; Gong, Han; Du, Min; Li, Tiange; Mao, Xueying (Frontiers in Nutrition, 2022)
Pre-pregnancy obesity and high-fat diet (HFD) during pregnancy and lactation are associated with neurodevelopmental delay in offspring. This study aimed to investigate whether milk fat globule membrane (MFGM) supplementation in obese dams could promote neurodevelopment in offspring. Obese female rats induced by HFD were supplemented with MFGM during pregnancy and lactation. Maternal HFD exposure significantly delayed the maturation of neurological reflexes and inhibited neurogenesis in offspring, which were significantly recovered by maternal MFGM supplementation. Gut microbiota analysis revealed that MFGM supplementation modulated the diversity and composition of gut microbiota in offspring. The abundance of pro-inflammatory bacteria such as Escherichia shigella and Enterococcus were down-regulated, and the abundance of bacteria with anti-inflammatory and anti-obesity functions, such as Akkermansia and Lactobacillus were up-regulated. Furthermore, MFGM alleviated neuroinflammation by decreasing the levels of lipopolysaccharides (LPS) and pro-inflammatory cytokines in the circulation and brain, as well as inhibiting the activation of microglia. Spearman’s correlation analysis suggested that there existed a correlation between gut microbiota and inflammation-related indexes. In conclusion, maternal MFGM supplementation promotes neurodevelopment partly via modulating gut microbiota in offspring.